The importance of a medical chaperone: a quality improvement study exploring the use of a note stamp in a tertiary breast surgery unit. Issue 7 (15th July 2015) - Rose, K; Eshelby, S; Thiruchelvam, P; Khoo, A; Hogben, K
Abstract : Objectives: The project aim was to determine current use and documentation of medical chaperones within a major breast service unit. It explored ways of improving adherence to professional guidelines concerning chaperones. Setting: The single centre quality improvement project was completed in a tertiary breast service unit in North West London. It was a three-stage project with initial audit in October 2013, 1st postintervention cycle in November 2013 and 2nd postintervention cycle in October 2014. Participants: In each study cycle, data were collected from entries in clinic notes until at least 155 encounters with documented clinical examination were analysed. All notes were of female patients. Interventions: (1) Intervention 1st cycle: presentation and discussion of chaperone guidelines alongside reminder posters and introduction of note stamp. (2) Intervention 2nd cycle: note stamp alone. Primary and secondary outcome measures: Documentation of chaperone offer, documentation of patient preference regarding chaperone, identifier (name or signature) of chaperone present and gender of examining clinician. Results: In the 1st postintervention cycle, 69.95% documentation of chaperone offer was recorded, p<0.001, CI (59.04% to 80.76%). This result was replicated in the 2nd postintervention cycle a year later with 74.86% documentation of chaperone offer recorded, p<0.001, CI (66.41% to 83.31%). The 4.91% difference was insignificant; p=0.294, CI (14.03% to 4.21%). Conclusions: The authors suggest that a proforma approach to medical chaperones is an effective means of ensuring adherence to best practice guidelines. A stamp, or similar, that can be embedded into documentation structure is an effective example of such an approach. Improved documentation allows any problems with adherence to guidelines to be more easily identified, helping to ensure the safeguarding of patients and staff involved in intimate examinations.